2017
DOI: 10.1007/s10456-017-9554-9
|View full text |Cite
|
Sign up to set email alerts
|

Pro-angiogenic capacities of microvesicles produced by skin wound myofibroblasts

Abstract: Wound healing is a very highly organized process where numerous cell types are tightly regulated to restore injured tissue. Myofibroblasts are cells that produce new extracellular matrix and contract wound edges. We previously reported that the human myofibroblasts isolated from normal wound (WMyos) produced microvesicles (MVs) in the presence of the serum. In this study, MVs were further characterized using a proteomic strategy and potential functions of the MVs were determined. MV proteins isolated from six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 37 publications
5
69
0
Order By: Relevance
“…However, reperfusion therapy also causes additional damage to the kidney tissue [47], which is defined as I/R injury in clinical practice [48]. In the present study, we explored the etiology of renal IR injury and found that the pathogenesis of kidney reperfusion damage was closely associated with Mst1 upregulation.…”
Section: Discussionmentioning
confidence: 75%
“…However, reperfusion therapy also causes additional damage to the kidney tissue [47], which is defined as I/R injury in clinical practice [48]. In the present study, we explored the etiology of renal IR injury and found that the pathogenesis of kidney reperfusion damage was closely associated with Mst1 upregulation.…”
Section: Discussionmentioning
confidence: 75%
“…The primary pathogenesis underlying diabetic nephropathy is the loss of functional cells and the accumulation of extracellular matrix (ECM). Excessive apoptosis of mesangial cells induces a fall in glomerular filtration, along with the thickness of the basement membrane and renal fibrosis [51]. The clinical outcome of diabetic nephropathy is urotoxin retention and metabolic substance accumulation [52].…”
Section: Discussionmentioning
confidence: 99%
“…While these 2D assays are sufficient to induce EC cord formation [7678], they cannot reproduce the necessary cues for true lumen formation found in native, 3D tissues. Collagen sandwich assays surround EC within a 3D matrix by seeding the cells in monolayer on collagen I matrix and then covering them with a second layer of collagen [79].…”
Section: 3d Models Of Vascular Morphogenesismentioning
confidence: 99%